Developing Local Wisdom-Based Instructional Materials in Minangkabau Context for English for Tourism Course - Zulhermindra Zulhermindra; Sirajul Munir; Nina Suzanne; Hadiarni Hadiarni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to develop a model of local wisdom-based instructional materials in Minangkabau context for the English for Tourism course. To realize the aim, an R&D design was applied by adapting Borg & Gall’s first four stages, namely product analysis, initial product development, expert validation, and product revision. Product analysis includes analyzing the characteristics and needs of students towards the teaching materials; b) interviews with competent resource persons to obtain input for initial product development; c) a review of the relevant theory of initial product development. Initial Product Development includes formulating core topics, designing syllabus, gathering resources for designing draft, and designing, editing and printing prototypes. Validation was conducted to figure out whether the prototype model had integrated Minangkabau local wisdom in teaching materials for the course and was suitable for learning into speaking. The product analysis stage resulted in initial product development in the form of a prototype consisting of 14 units, where each unit consists of 4 parts, namely: introduction, common expressions, sample conversations, and role play. The validation results confirm that, in general, in terms of the relevance of teaching materials to course objectives, the prototype was valid (3.15 out of 4) and very valid (4.03 out of 5). In addition, in terms of the principles of learning speaking skills, the prototype was very valid (3.66 out of 4). Furthermore, from the aspect of integrating Minangkabau local wisdom into teaching materials, this prototype has provided a model for practical conversations for tour guiding activities in Minangkabau context.